Geological Structure Identification Using GGMplus Satellite Gravity Data in The Area Surrounding Mount Tampomas - Mazzaluna, Haidar Prida; Rustadi; Wibowo, Rahmat Catur (BRIN Publishing, 2024)
Satellite gravity provides a new alternative in geological exploration with several advantages, such as low operational cost and large covering area. GGMplus satellite gravity data provide better accuracy for several applications such as lithology or fault identification. Satellite gravity provides a new alternative in geological exploration with several advantages, such as lower costs, broader area coverage, and easily accessible data. Mount Tampomas is one of the areas that has geothermal prospects and a mountain area that has many types of rock formations and faults. This research has been conducted using GGMplus satellite gravity data in the Mount Tampomas area to obtain the second vertical derivative (SVD) and identify the fault distribution in the area. The GGMplus Gravity Acceleration data was corrected and filtered to obtain SVD structures in the area. The structure in this area is dominantly trending northwest-southeast and west-east. The area around Mount Tampomas forms a structure in the form of a caldera. In addition, there are also structures trending north-south at coordinates 81500-82000 E. Some of these structures were overlaid with a geological map to see the suitability of the processed data with the geological conditions that have been studied. The comparison is done by overlaying the structure of the interpretation results and the contour of the value 0 from the Second Vertical Derivative (SVD) data so that we get four fault structures that correlate with the geological map, three calderas, and one lineament that correlates with the lineament map.